2018
DOI: 10.3390/jintelligence6030032
|View full text |Cite
|
Sign up to set email alerts
|

Ability Tests Measure Personality, Personality Tests Measure Ability: Disentangling Construct and Method in Evaluating the Relationship between Personality and Ability

Abstract: Abstract:Although personality and cognitive ability are separate (sets of) constructs, we argue and demonstrate in this article that their effects are difficult to tease apart, because personality affects performance on cognitive tests and cognitive ability affects item responses on personality assessments. Cognitive ability is typically measured with tests of items with correct answers; personality is typically measured with rating-scale self-reports. Oftentimes conclusions regarding the personality-ability r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 158 publications
0
14
0
Order By: Relevance
“…In order to assess risk propensity, self-report questionnaires represent the most frequently employed approach (e.g., Johnson et al, 2004). In addition, objective tests (see Lejuez et al, 2002;Ortner and Proyer, 2015;Kyllonen and Kell, 2018) assess test takers' behavior in standardized miniature situations and quantify risky behavior in terms of behavior samples.…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess risk propensity, self-report questionnaires represent the most frequently employed approach (e.g., Johnson et al, 2004). In addition, objective tests (see Lejuez et al, 2002;Ortner and Proyer, 2015;Kyllonen and Kell, 2018) assess test takers' behavior in standardized miniature situations and quantify risky behavior in terms of behavior samples.…”
Section: Introductionmentioning
confidence: 99%
“…Item-20 was about the website accuracy in calculating the SAW method and showed the right recommendations. This research had succeeded in being a solution to the limitations of Ihsan and Furnham"s research [21]; Boitshwarelo, Reedy, and Billany"s research [22]; Kyllonen and Kell"s research [23]; Mariš"s research [24]; and Elmahdi, Al-Hattami, and Fawzi"s research [25]. The solution was the Stake model evaluation website implementation at Vocational Schools of IT in Bali.…”
Section: Methodsmentioning
confidence: 99%
“…Their research only focuses on the cognitive domain as measured by using an online test. Research was conducted in 2018 by Kyllonen and Kell [23] showed a test measuring cognitive ability and personality measurement. Measurement of cognitive abilities was measured using cognitive tests, such as multiple choice and essays.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the enumerated thematic topics, for this Special Issue, we also explicitly invited the submission of theory papers, for instance, the relevance of the Brunswik symmetry for a proper study of the interplay between intelligence and personality—the correlation values between both constructs are remarkably different across levels of generality [9]; the relations between intelligence and personality at the facet level [10]; how we view intelligence–personality relations [11]; the nature of our measurements of intelligence and personality [12]; the relevance of broadening the way we measure personality to study its relationships with intelligence constructs [13]; and the developmental interplay between openness and ability in a microlevel extension of the Openness-Fluid-Crystallized-Intelligence (OFCI) model [14].…”
mentioning
confidence: 99%
“…In this regard, Stankov [13] suggests that we must increase the scope of the personality construct, moving beyond the lexical approach that characterizes the Big Five model. Kyllonen and Kell [12] show that intelligence is involved in personality assessment (and the other way around): “conclusions regarding the ability-personality relationship have as much to do with measurement methods as with construct similarities and differences”. Thus, we can conclude that it is worthwhile to reconsider the actual breadth of constructs considered, as well as the way they are assessed.…”
mentioning
confidence: 99%